2001
DOI: 10.1073/pnas.051627998
|View full text |Cite
|
Sign up to set email alerts
|

Two different neurodegenerative diseases caused by proteins with similar structures

Abstract: The downstream prion-like protein (doppel, or Dpl) is a paralog of the cellular prion protein, PrP C . The two proteins have Ϸ25% sequence identity, but seem to have distinct physiologic roles. Unlike PrP C , Dpl does not support prion replication; instead, overexpression of Dpl in the brain seems to cause a completely different neurodegenerative disease. We report the solution structure of a fragment of recombinant mouse Dpl (residues 26 -157) containing a globular domain with three helices and a small amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
1
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 45 publications
2
109
1
3
Order By: Relevance
“…In fact, Dpl-mediated toxicity of PCs is reversed by the introduction of WT PrP c (Yamaguchi et al, 2004). However, the role of Dpl is not clear since it shows low expression in adult brain and the studies performed to date have focused on its roles during development and in other organs (Behrens and Aguzzi, 2002) and also its functions in prion pathogenesis (Behrens et al, 2001;Mo et al, 2001) Dpl protein shares with PrP c the C-terminal portion of the molecule but lacks the OR and CD, although it conserves the GPI anchor (Moore et al, 1999). On the basis of these observations, several studies were directed to analyzing the phenotype of mice expressing truncated forms of PrP c (lacking some portions of the N-terminal domains).…”
Section: Other Prp C Mutant Mice: the Puzzle Of Functions Increasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Dpl-mediated toxicity of PCs is reversed by the introduction of WT PrP c (Yamaguchi et al, 2004). However, the role of Dpl is not clear since it shows low expression in adult brain and the studies performed to date have focused on its roles during development and in other organs (Behrens and Aguzzi, 2002) and also its functions in prion pathogenesis (Behrens et al, 2001;Mo et al, 2001) Dpl protein shares with PrP c the C-terminal portion of the molecule but lacks the OR and CD, although it conserves the GPI anchor (Moore et al, 1999). On the basis of these observations, several studies were directed to analyzing the phenotype of mice expressing truncated forms of PrP c (lacking some portions of the N-terminal domains).…”
Section: Other Prp C Mutant Mice: the Puzzle Of Functions Increasesmentioning
confidence: 99%
“…However, these studies are subject to debate since the requirement of PrP c expression for synthetic peptide toxicity is controversial (see for example (Brown, 2000;Fioriti et al, 2005;Gavin et al, 2005;Kunz et al, 1999;Singh et al, 2002)). N-terminally truncated constructions, like F35 or Dpl protein, lack residues 105-125 (Luhrs et al, 2003;Mo et al, 2001;Shmerling et al, 1998). F35 and Dpl overexpression promotes neural cell death in several mouse models, thereby implicating the 105-125 region in survival signaling and indicating that its absence promotes the activation of several death-related pathways.…”
Section: Dissecting Prp C Domains and Cell Death: The Central Domainmentioning
confidence: 99%
“…2 El prión PrP Sc se deriva de la isoforma celular benigna PrP C mediante un proceso postranslacional que involucra un cambio profundo en la conformación. 4 Aunque algunos casos de ECJ se deben a mutaciones en el gen que codifica la PrP, es decir, son hereditarios, otros (con muy baja frecuencia) se deben a la transmisión de EEB a humanos por medio del alimento. 2,5 Sin embargo, se piensa que la mayoría de los casos son causa de la generación del prión de novo.…”
Section: Priones Y Enfermedades Espongiformes Transmisiblesunclassified
“…3 Por ello, se presume que el paso de PrP C a PrP Sc se da por replegamiento dirigido. 4 Es decir, puede haber otra u otras moléculas involucradas en el fenómeno.…”
Section: Noticias Salud Pública De México / Vol43 No3 Mayo-junio unclassified
“…The protein structural analysis clearly showed that PrPLP/ Dpl is a structural homologue of the C-terminal globular domain of PrP C , composed of three α-helices and two short antiparallel β-strands ( Fig. 1) (21).…”
Section: Prplp/dpl and Prpmentioning
confidence: 99%